2008
DOI: 10.1152/ajplung.00381.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human airway smooth muscle cell proliferation by β2-adrenergic receptors and cAMP is PKA independent: evidence for EPAC involvement

Abstract: Mechanisms by which beta-adrenergic receptor (beta AR) agonists inhibit proliferation of human airway smooth muscle (HASM) cells were investigated because of their potential relevance to smooth muscle hyperplasia in asthma. We hypothesized that beta AR agonists would inhibit mitogenesis in HASM cells via the beta 2AR, an increase in cAMP, and PKA activation. HASM cells were treated for 24 h with various agents and then analyzed for [3H]thymidine incorporation as a measure of cell proliferation. EGF stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 32 publications
2
69
0
1
Order By: Relevance
“…Epac itself or together with its target Rap has been implicated in the control of cell proliferation, and another major cAMP target, protein kinase A (PKA), was shown to act synergistically with these proteins in this process in several cases. [52][53][54][55][56][57] Our observation underlines the link between Epac, Rap, PKA and the cell cycle. However, further investigations are needed to determine whether their effects in HUVECs are proliferative or anti-proliferative and Rap-or PKA-dependent.…”
Section: Cid-msa Etd and Hcd Have Complementary Contributions To Phosupporting
confidence: 55%
“…Epac itself or together with its target Rap has been implicated in the control of cell proliferation, and another major cAMP target, protein kinase A (PKA), was shown to act synergistically with these proteins in this process in several cases. [52][53][54][55][56][57] Our observation underlines the link between Epac, Rap, PKA and the cell cycle. However, further investigations are needed to determine whether their effects in HUVECs are proliferative or anti-proliferative and Rap-or PKA-dependent.…”
Section: Cid-msa Etd and Hcd Have Complementary Contributions To Phosupporting
confidence: 55%
“…These findings were independent of the growth factor/ medium conditions used. This novel anti-proliferative role for Epac-1 in primary lung fibroblasts is supported by a recent study that suggests Epac may also be anti-proliferative in bronchial smooth muscle cells (46). The ability of Epac-1 (and subsequent activation of Rap1) to play divergent roles in mesenchymal cells versus other cell types illustrates how these cells can exhibit dichotomous responses to common signaling pathways.…”
Section: Discussionmentioning
confidence: 76%
“…66,67 Similarly, direct activators of EPAC, also inhibit mitogen-induced proliferation of cultured air way smooth muscle cells suggesting that EPAC activation may limit the remodeling observed in diseases of the airways, such as asthma and chronic obstructive pulmonary disease. 68,69 This effect of EPAC, at least in rat VSMCs, is synergistic with PKA and involves coordinated inhibition of the immediate response gene Early growth response 1 and other factors such as cyclin D1 and S-phase kinase-associated protein-2 (Skp2), that are critical for regulating cell-cycle progression ( Figure 5). 66,70 Recently, it has been reported that therapeutically relevant concentrations of the prostacyclin analog, beraprost can inhibit PDGF-induced human VSMC migration via activation of the cAMP effector EPAC.…”
Section: Regulation Of the Vsmc Proliferation And Migrationmentioning
confidence: 99%